2020
DOI: 10.1371/journal.pone.0231560
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Corynebacterium glutamicum dehydroshikimate dehydratase QsuB and its potential for microbial production of protocatechuic acid

Abstract: The dehydroshikimate dehydratase (DSD) from Corynebacterium glutamicum encoded by the qsuB gene is related to the previously described QuiC1 protein (39.9% identity) from Pseudomonas putida. Both QuiC1 and QsuB are two-domain bacterial DSDs. The N-terminal domain provides dehydratase activity, while the C-terminal domain has sequence identity with 4-hydroxyphenylpyruvate dioxygenase. Here, the QsuB protein and its N-terminal domain (N-QsuB) were expressed in the T7 system, purified and characterized. QsuB was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…The decrease of the PCA formation rate towards the end of the cultivation could be attributed to the reduced activity of 3-dehydroshikimate dehydratase (QsuB). Previous in vitro analysis of the substrate-saturated QsuB enzyme from C. glutamicum showed non-competitive inhibition ( K I = 0.96 mM) at a concentration of 0.6 mM PCA [45]. Further in vitro analysis of this enzyme showed its highest activity in presence of 1 mM Co 2+ and at a pH of 8.0 ± 8.4.…”
Section: Resultsmentioning
confidence: 91%
“…The decrease of the PCA formation rate towards the end of the cultivation could be attributed to the reduced activity of 3-dehydroshikimate dehydratase (QsuB). Previous in vitro analysis of the substrate-saturated QsuB enzyme from C. glutamicum showed non-competitive inhibition ( K I = 0.96 mM) at a concentration of 0.6 mM PCA [45]. Further in vitro analysis of this enzyme showed its highest activity in presence of 1 mM Co 2+ and at a pH of 8.0 ± 8.4.…”
Section: Resultsmentioning
confidence: 91%
“…Multiple DSD variants from fungi, Acinetobacter species, Bacillus species, and Pseudomonas species have been identified. Earlier studies have reported the use of DSD from Corynebacterium glutamicum , Podospora pauciseta , and Klebsiella pneumonia ( Hansen et al, 2009 ; Curran et al, 2013 ; Shmonova et al, 2020 ; Table 1 ). In this study, the P. putida DSD gene was cloned and expressed in E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis is constrained in two different ways: (i) the PEP flux to the phosphotransferase system (PTS) ( Rodriguez et al, 2014 ), and (ii) the feedback inhibition of the three DAHP synthase enzymes AroG, AroF and AroH by phenylalanine, tyrosine and tryptophan, respectively ( Johansson and Lidén, 2006 ). Further limitations of PCA production through the shikimate pathway are ascribed to the product toxicity to the cells and inhibition of the DSD enzyme, resulting in termination of the process ( Pugh et al, 2014 ; Shmonova et al, 2020 ). Addition of 1.5 g/L PCA to Escherichia coli culture has been shown to completely impair cell growth ( Pugh et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations